Teachers’ Perceived Usefulness and Perceived Ease of Use of Technology in Primary School Classrooms in Bangladesh (Teacher’s World: Journal of Education and Research, 2024)
The study aimed to investigate primary school teachers’ knowledge, attitudes, and practices (KAP) regarding technology use in the classroom in five selected districts of Bangladesh. Data was collected through in-depth interviews and focus group discussions with primary school teachers, local education officers, and PTI and URC instructors. Incorporating the theoretical lens of the Technology Acceptance Model (TAM), the study examined the perceived usefulness (PU) and perceived ease-of-use (PEOU) of ICT among teachers. Findings indicated that while teachers recognize the high usefulness of ICT in educational settings, they report lower ease-of-use, often attributable to factors like inadequate training, infrastructure and limited resources. Technology-based teaching and learning activities could enhance the quality of education and promote equity and inclusiveness in primary schools. The COVID-19 pandemic significantly influenced ICT practice in government primary schools, leading to the adoption of mobile-based teaching-learning practices. The study recommends targeted interventions emphasizing comprehensive teacher training, infrastructural enhancements, and motivational strategies are crucial to bridge the policy-practice gap regarding ICT. Teacher’s World: Journal of Education and Research, 49 (2),109-124